2019
DOI: 10.1186/s12935-018-0724-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 6-gene signature predicting prognosis for colorectal cancer

Abstract: BackgroundAn accurate and robust gene signature is of the utmost importance in assisting oncologists to make a more accurate evaluation in clinical practice. In our study, we extracted key mRNAs significantly related to colorectal cancer (CRC) prognosis and we constructed an expression-based gene signature to predict CRC patients’ survival.MethodsmRNA expression profiles and clinicopathological data of colon adenocarcinoma (COAD) cases and rectum adenocarcinoma (READ) were collected from The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 37 publications
0
72
0
Order By: Relevance
“…Although the number of genes in prognostic signatures had a decreasing trend as a whole [50,51], most of the previous prognostic signatures were often in the form of a union set of dozens or hundreds of genes, or even a network module [6,[52][53][54]. This would considerably weaken the importance of individual genes, which may be one of the reasons why the four network centralities of the single PG were not high.…”
Section: Resultsmentioning
confidence: 99%
“…Although the number of genes in prognostic signatures had a decreasing trend as a whole [50,51], most of the previous prognostic signatures were often in the form of a union set of dozens or hundreds of genes, or even a network module [6,[52][53][54]. This would considerably weaken the importance of individual genes, which may be one of the reasons why the four network centralities of the single PG were not high.…”
Section: Resultsmentioning
confidence: 99%
“…MAI; they are shown in table III.To further validate our findings, the saturation analyses of cancer genes across 33 tumor types (except for COAD) are obtained from the TumorPortal [26]. Validation for the COAD cancer follows a signature-based approach [3], which was used for predicting the progression of colorectal cancer. However, our approach makes some false identifications, as 21 out of 25 genes are validated to be correct, making only 4 false identifications.…”
Section: B Feature Importance and Validation Of Top Biomarkersmentioning
confidence: 85%
“…Since intensities did not follow any regular pattern, we chose top 660 genes across 33 tumor types (top-20 genes per class) as more significant based on the measure of MAI. Since we have more than 20K protein-coding genes, our choice of 660 is still a reasonable choice, since the number of important biomarkers should be small whose GE changes are sensitive to cancer growth [3]. All genes in the top-20 list can thus be viewed as tumor-specific biomarkers, which contribute most toward making the predictions.…”
Section: B Feature Importance and Validation Of Top Biomarkersmentioning
confidence: 99%
“…Moreover, knockdown of TIMP1 leads to decreased proliferation of HT29 cells [39]. Huang [40], Zeng [41], and Zuo [42] et al demonstrated that the expression levels of TIMP1 may be negatively correlated with the prognosis of COAD patients. Song et al [43] found that TIMP1 knockdown could result in decreased proliferation, migration, and invasion as well as increased apoptosis in vitro, whereas there is weakened tumorigenesis and metastasis in vivo via the FAK-PI3K/Akt and MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%